Kinship ecology and the bildungsroman: the child–animal relationship in Louise Erdrich's The Birchbark House series. Issue 3 (4th March 2022) - Sparks, Angela
ABSTRACT: This paper addresses the question of what it means to be human from a Native American (specifically, Ojibwe) perspective by interrogating the human-animal relationships in  The Birchbark House  series by Louise Erdrich (1999–2016). The article begins by considering the human-nature ontology shared by Native American tribes, before developing the idea of a kinship ecology within an Ojibwe context. The novels' designation as children's literature adds further complexity to this study due to its tendency towards didacticism and the nature of the child 'learning' to be human and about their place in the world. Furthermore, within the novels there exists a counterpoint to the author's portrayal of Ojibwe values through the impact of settler colonialism on the lives of the characters, and with it, the differing treatment of animals and the wider environment. I consider how the novels' presentation of Ojibwe 'human nature' is at odds with settler colonialist beliefs about what it means to be human, both in the historical setting of the narrative and in the novels' message for the twenty-first century reader.